A Combined Process for Char Activation and Calcium Oxide Formation from Calcium Carbonate - Mohd Noor, Nur Izzatul A’liah (IRC, 2015)
In this study, the pattern of carbon dioxide generation from calcination of calcium carbonate are studied at different temperatures 600, 700 and 800oC. Besides, the morphology of activated char from the combination process of pyrolysis and calcination of calcium carbonate are investigated as the part of the objectives in this project. This project mainly focuses on synthesizing the products of pyrolysis that is biochar and product of calcination that is calcium oxide to produce activated char. To perform this experiment, the limestone with 600 mesh are calcined together with RWS biochar from pyrolysis in a tube furnace at 600, 700 and 800oC. The carbon dioxide released from the calcination of limestone are used by the biochar to convert itself into activated char. The properties of activated char are studied by performing Scanning Electron Microscopy (SEM) and Fourier Transformation Infrared (FTIR) analysis. From this project, it can be concluded from FTIR analysis that O–H stretch, H–bonded and C-H stretch is decreasing as the temperature increasing. From the SEM images generated that under extensive heating, particle size of the bio-char decreased due to breakage and shrinkage mechanisms. It can be seen that the carbon and nitrogen in the samples are decreasing with increasing of calcination temperature, while oxygen shows the opposite pattern.